Multiple Information Signals in the Market for Charitable Donations - Harris, Erica E.; Neely, Daniel G. (Contemporary Accounting Research, 2016)
Abstract We find evidence indicating that donors use third‐party rating information when they donate to U.S. nonprofit organizations (nonprofits). Specifically, using a sample of over 3,800 unique nonprofits rated by the three largest charity rating organizations in 2007, and over 12,000 unrated control nonprofits, we find that rated nonprofits have significantly higher direct donations than unrated charities. We also hypothesize and find that nonprofits with ratings from multiple rating organizations receive incrementally higher levels of donations. In addition, although charities that receive a positive rating have higher levels of donor support than those receiving a negative rating, both positively and negatively rated nonprofits receive a higher level of direct donations than unrated nonprofits. Finally, we find that nonprofits with consistently good ratings receive higher donations than those with mixed or consistently negative ratings, indicating the donor community values consistency across the three rating agencies.